PENGELOLAAN TAMAN NASIONAL ZAMRUD DI KABUPATEN SIAK - Yesi Febri Rahmadani; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Zamrud National Park was appointed through the Decree of the Minister of Environment and Forestry Number 350 / Menlhk / Setjen / PLA.2 / 5/2016 on May 4, 2016 with an area of 31,480 ha. The phenomenon in this problem is that there is still a lot of damage that occurs in the Zamrud National Park area and also access to the area that is not yet available. This study aims to determine how the management of the Zamrud National Park and what are the factors that influence the management of the Zamrud National Park. The theoretical concept used in this research is G.R Terry's management theory which consists of planning, organizing, implementing and monitoring. This research uses qualitative research methods and descriptive analysis of data. Data collection techniques using interview techniques, observation and documentation using informants as a source of information. The results of the study indicate that the management of Zamrud National Park by the Riau Natural Resources Conservation Center (BBKSDA) has been running but it is still not optimal because there are still several deficiencies in the management. One of the challenges faced by the Riau Natural Resources Conservation Center (BBKSDA) is because the Zamrud National Park area has a high level of forest and land fire vulnerability. Keywords: Management, Zamrud National Park, Peat Swamp